Peningkatan Hasil Belajar Pada Materi Statistika (Kuartil, Desil, Persentil) dengan Pendekatan Konstruktivisme (psnppg, 2024)
This study aims to determine whether the Constructivism approach can improve student learning outcomes in Statistics, specifically in the subtopics of quartiles, deciles, and percentiles, for class X2 students at SMA N 14 Semarang during the 2023/2024 academic year. This classroom action research was conducted in two cycles, with four main stages: planning, implementation, observation, and reflection. Data were collected through post-tests, observation sheets, and documentation. The results showed that the application of the Constructivism approach successfully improved Mathematics learning outcomes, particularly in the topics of quartiles, deciles, and percentiles. This improvement was evident in both cycles I and II, with the average pre-test and post-test scores showing an increase. In cycle I, the average pre-test score was 44.1, while the average post-test score was 74.1. In cycle II, the average pre-test score increased to 74.1, and the average post-test score reached 80.2. Thus, the Constructivism approach can enhance student learning outcomes.
Keywords: Learning Outcomes; Constructivist Approach; Mathematics